SAT0220 USE OF TOCILIZUMAB IN AORTITIS. A MULTICENTER STUDY OF 79 PATIENTS. (June 2019) - Calderón-Goercke, Monica; Loricera, J.; Prieto-Peña, D.; Aldasoro, Vicente; Castañeda, Santos; Villa-Blanco, Ignacio; Humbría, Alicia; Moriano, Clara; Romero-Yuste, Susana; Narváez, J.; Gomez-Arango, Catalina; Perez-Pampín, Eva; et al.
Abstract : Background: Aortitis can be idiopathic or associated with other conditions. It is frequently refractory to conventional immunosuppressive therapy. Tocilizumab (TCZ), an anti-IL-6 receptor antibody seems to be effective and safe. Objectives: Our aim was to assess the efficacy and safety of TCZ at short and long follow-up in a series of patients with Aortitis. Methods: Retrospective, multicenter study of 79 patients diagnosed of inflammatory aortitis based on imaging techniques (PET/CT, CT angiography and/or MR angiography). Results: We study 79 patients (61 w/ 18 m). 59 (74.7%) cases were Aortitis secondary to Giant Cell Arteritis (GCA), while 20 (25.3%) were idiopathic. The mean age was 71±8.5 years vs 64.2±7.1 years, respectively (p=0.001). At time of disease diagnosis more than a half of patients (59.5%) presented as main symptom polymyalgia rheumatica (PMR). Aortitis was diagnosed with PET/CT (71 patients), angioRMN (12 patients) and angioCT (8 patients). Prior to TCZ treatment, 61 (77.2%) patients had received conventional immunosuppressive drugs, 59 (74.7%) of them received MTX. After 24 months of treatment with TCZ, more than 75% of patients reached a prolonged remission in both groups (p=0.527), with only 4% of relapses after the same follow-up period (p=1.000). 40 (50.6%) patients had a control image technique (PET/CT) throughout follow up. 4 (3 secondary to GCA and 1 idiopathic) patients reached a complete improvement in uptake after one year of treatment. Conclusion: Our results show that idiopathic aortitis occurs in younger patients compared with aortitis secondary to GCA. TCZ proved to be effective in both pathologies, allowing clinical and analytical improvement, as well as a reduction of corticoid dose, without increasing the risk of relapse. However, the improvement in imaging techniques seems to be slower. Reference: [1] Loricera J, Blanco R, Castañeda S, Humbría A, Ortego-Centeno N, Narváez J, et al. Tocilizumab in refractory aortitis: study on 16 patients and literature review. Clin Exp Rheumatol. 2014; 32:79-89. Disclosure of Interests: Monica Calderón-Goercke: None declared, J. Loricera: None declared, D. Prieto-Peña: None declared, Vicente Aldasoro: None declared, Santos Castañeda Consultant for: Amgen, BMS, Pfizer, Lilly, MSD, Roche, Sanofi, UCB, Ignacio Villa-Blanco: None declared, Alicia Humbría: None declared, Clara Moriano: None declared, Susana Romero-Yuste: None declared, J. Narváez Consultant for: Bristol-Myers Squibb, Catalina Gomez-Arango: None declared, Eva Perez-Pampín: None declared, Rafael Melero: None declared, Marcelino Revenga: None declared, Noelia Alvarez-Rivas: None declared, Francisca Sivera: None declared, María Álvarez del Buergo: None declared, Luisa Marena Rojas: None declared, Eva Galindez: None declared, Beatriz Arca: None declared, Roser Solans-Laqué: None declared, Carlos Vázquez: None declared, Pau Lluch: None declared, Eva Salgado-Pérez: None declared, Cristina Luna-Gomez: None declared, Francisco J. Toyos Sáenz de Miera: None declared, Nagore Fernández-Llanio: None declared, Antonio García: None declared, Carmen Larena: None declared, Natalia Palmou-Fontana: None declared, Vanesa Calvo-Río: None declared, Carmen González-Vela: None declared, Alfonso Corrales: None declared, María Varela-García: None declared, Elena Aurrecoechea: None declared, Raquel Dos-Santos: None declared, José Luis Martín-Varillas: None declared, Sabela Fernández: None declared, J. Luis Hernández: None declared, Miguel A González-Gay Grant/research support from: Prof. MA Gonzalez-Gay received grants/research supports from Abbvie, MSD, Jansen and Roche., Speakers bureau: Consultation fees/participation in company sponsored speaker's bureau from Pfizer, Lilly, Sobi, Celgene, Novartis, Roche and Sanofi., Ricardo Blanco Grant/research support from: Abbvie, MSD, and Roche, Consultant for: Abbvie, Pfizer, Roche, Bristol-Myers, Janssen, Speakers bureau: Abbvie, Pfizer, Roche, Bristol-Myers, Janssen